2002
DOI: 10.1097/00126334-200209010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary HIV Counseling and Testing: Experience Among the Sexually Active Population in Bangui, Central African Republic

Abstract: This experience demonstrates that VCT for HIV infection is feasible in Central Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…The efficacy of HIV counseling and testing as a HIV risk behavior reduction strategy has been demonstrated in a randomized multi-center trial that included sites in sub-Saharan Africa and the Caribbean (The Voluntary HIV-1 Counseling and Testing Efficacy Study Group, 2000). Several other studies also have shown reductions in HIV risk behavior following counseling and testing (Gresenguet et al, 2002;De Zoysa et al, 1995;Muller et al, 1992;Higgins et al, 1991;Allen et al, 1992).…”
Section: Introductionmentioning
confidence: 96%
“…The efficacy of HIV counseling and testing as a HIV risk behavior reduction strategy has been demonstrated in a randomized multi-center trial that included sites in sub-Saharan Africa and the Caribbean (The Voluntary HIV-1 Counseling and Testing Efficacy Study Group, 2000). Several other studies also have shown reductions in HIV risk behavior following counseling and testing (Gresenguet et al, 2002;De Zoysa et al, 1995;Muller et al, 1992;Higgins et al, 1991;Allen et al, 1992).…”
Section: Introductionmentioning
confidence: 96%
“…Studies of HIV testing preparedness and acceptance have identified a number of knowledge and behavioral risk correlates, such as perceptions of the disease (Castle, 2003;Tharawan et al, 2003), attitudes toward testing (Kalichman and Simbayi, 2003), perceived risk (Fylkesnes and Siziya, 2004), presence of STI symptoms and absence of condom use (Gresenguet et al, 2002). The relative importance of HIV knowledge, attitudes and risk behaviors for HIV test acceptability is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that offering free tests for HIV infection was a significant factor in determining whether individuals chose to undergo testing (Grésenguet et al, 2002). However, because tests for HIV infection were offered free of charge to participants, the cost of testing did not determine whether subjects elected to undergo testing in the present study.…”
Section: Discussionmentioning
confidence: 79%